The city of San Miguel in its historical landscape - Vela Cossío, Fernando (2012)
San Miguel was the first Spanish establishment in the southwestern hemisphere. Its founding dates from 1532; it was first known by the name San Miguel de Tangará. It was soon relocated to a second settlement in Alto Piura where, between 1534-1580, it became a significant urban center of which a complete city map of some 10,000 square meters was created around its main square (Plaza de Armas). This study presents an overview of San Miguel city in its historic context.